2021
DOI: 10.3390/ijerph18041586
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Food Safety Compliance and Hygiene Practices of Food Handlers Working in Community and Healthcare Settings in Kuwait

Abstract: Safe food handling and proper hygiene practices performed by food handlers (FHs) in catering establishments are fundamental elements in reducing foodborne diseases. This study aimed at assessing food safety knowledge and compliance of hygiene practices of FHs within food establishments (using a structured questionnaire). A cross-sectional study was carried out from May 2016 to March 2018 on FHs working in community and healthcare settings. A total of 405 FHs, including 44.9% and 55.1%, were working in communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…50 A medical examination should be required before beginning to work with food. 51 This is due to the fact that food handlers who had their health status checked had a better understanding of safe food handling. During their medical checkups, they also received professional advice, which improved their overall food handling performance.…”
Section: Discussionmentioning
confidence: 99%
“…50 A medical examination should be required before beginning to work with food. 51 This is due to the fact that food handlers who had their health status checked had a better understanding of safe food handling. During their medical checkups, they also received professional advice, which improved their overall food handling performance.…”
Section: Discussionmentioning
confidence: 99%
“…Representatives of carbapenem-resistant E. coli and K. pneumoniae isolates with carbapenemase-positive ( n = 2) and carbapenemase-negative ( n = 2) for each were chosen to gain further insight into the origin of genetic diversity and investigate resistance mechanisms. Sample collection and isolation methods were previously described [ 19 , 20 ]. Isolates were identified by VITEK 2 ID system (bioMérieux, Marcy-l’Etoile, France) and antimicrobial susceptibility testing was carried out to determine the minimum inhibitory concentration (MIC) in μg/mL against 19 antibiotics using the Epsilometer test ( E test) (bioMérieux, Marcy-l’Etoile, France), except for colistin, which was tested by agar dilution method as described previously [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, Araújo et al ( 37 ) identified 62.9% of male handlers in 37 community restaurants in Braz. Moghnia et al ( 38 ) reported 84.7% of male handlers in community restaurants and health centers in six Kuwait provinces.…”
Section: Discussionmentioning
confidence: 99%